Determinants of urban households’ livelihood diversification strategies in North Shewa Zone, Ethiopia - Girma Mulugeta Emeru; Abebaw Hailu Fikire; Zemenu Bires Beza (Cogent Economics & Finance)
Livelihood diversification is important for urban development to end poverty and food insecurity problems. In Ethiopia, urban livelihood diversification is quite low specifically in North Shewa Zone. Therefore, this study aims to identify the determinants of livelihood diversification strategies for urban households in the North Shewa Zone. The data were collected through both primary and secondary data collection methods. A multistage sampling technique was employed to select 398 household heads from three urban areas of the North Shewa Zone. A multinomial logistic regression model was employed to analyze the determinant of livelihood diversification strategies in the study area. The results of the model revealed that livelihood diversification strategies were determined by the age of the household head, education status, family size, credit access, market access, and training and extension service positively and the dependency ratio was negative. The study recommends that the zonal and regional governments of Ethiopia should develop a comprehensive urban development policy that could empower off-farm and non-farm urban livelihood diversification strategies besides the farm activities.